Life cycle assessment pabrik semen PT Holcim Indonesia Tbk. pabrik Cilacap: komparasi antara bahan bakar batubara dengan biomassa - Taufan Ratri Harjanto; Moh. Fahrurrozi; I Made Bendiyasa (Jurnal Rekayasa Proses, 2012)
Holcim Indonesia Tbk. Cilacap having capacity of 2.6 million ton/year uses rice husk as alternative fuels. The utilization of the rice husk will effect the environment. The aim of the study is to evaluate the effects of biomass utilization to environment using life cycle assessment (LCA) method.The “cradle to gate” approach was used to evaluate four scenarios of different fuel combinations: (1) 100% coal, (2) mixed fuel of 90% coal and 10% biomass, (3) mixed fuel of 50% coal and 50% biomass, (4) 100% biomass as primary fuels in the kiln for 1000 kg cement. Evaluation of environment impact related to each scenario was using ISO 14040 (2006) that consists of: (1) goal definition and scoping, (2) inventory analysis, (3) impact assessment, and (4) interpretation.Results showed by contribution analysis, the scenario 1, 2, 3, and 4, give 2.78 x10-1 Pt, 2.24 x10-1Pt, 1.57 x10-1Pt, and 8.50 x10-2 Pt respectively. It was also found that the global warming, respiratory inorganic and resources give significant impacts to the environment. It is suggested to replace silica tranportation using train, to utilize miscanthus giganteus and to grow plants or reforestry.